Sistem Pemilihan Karyawan Terbaik Menggunakan Metode TOPSIS - Nasution, Musri Iskandar; Fadlil, Abdul; Sunardi, S (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Merapi Online Corporation is a company located in Yogyakarta which is engaged in internet access services. Merapi Online Corporation gives rewards by selecting the best employees based on criteria as a provision of the company. This study designed a system to determine the best employee selection using a Decision Support System (DSS) with the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method has the principle chosen because it has the shortest distance to positive ideal solution and the farthest distance from the negative ideal solution from a geometric point of view using Euclidean distance to determine the relative closeness of choice with the best solution. The stages of this research are the collection of employee and criteria data, then weighting the criteria and assessment, after that the calculation uses the TOPSIS method, and the final step is the analysis of the calculation results. The criteria used in this study are attendance, years of service, permission, and discipline. Research has been successfully carried out on a sample of four employees for ease in presenting the data. The results of this study obtained the preferences of each employee, which is then ranked. The biggest preference value is chosen to be the best employee.